Structural, Functional, and Cellular Analysis of a Case of Acute Zonal Occult Outer Retinopathy (AZOOR) - Mattia Iuliano; Marco Lombardo; Benedetto Falsini; Jacopo Sebastiani; Michele D’Ambrosio; Francesco Martelli; Andrea Cusumano (Biomedicines, 2025)
Background: Adaptive optics transscleral flood illumination (AO-TFI) enables in vivo, non-invasive, high-resolution imaging of retinal pigment epithelium (RPE) and photoreceptor (PR) cells, paving the way for a new potential characterization of retinal diseases. This study aimed to analyze RPE and PR cells in a case of acute zonal occult outer retinopathy (AZOOR) using AO-TFI. Methods: A patient affected by AZOOR underwent a comprehensive eye examination, perimetry, electroretinography (ERG), autofluorescence, and optical coherence tomography (OCT) during the acute phase (T0). After three years (T1), OCT angiography (OCTA) and AO-TFI were also performed. Voronoi analysis was utilized to quantify RPE and PR cells. Results: At T0, OCT revealed interruptions in the ellipsoid zone (EZ) of the right eye, while the structure of the left eye appeared normal. Perimetry and ERG were abnormal in both eyes. At T1, OCT indicated recovery of the EZ in the right eye, while thinning of the ONL persisted. Perimetry and mfERG values remained below normative limits. OCTA exhibited globally reduced vessel density in the inner retina of the right eye. AO-TFI demonstrated reduced PR density in affected areas despite preserved EZ, while RPE cell density appeared unaffected. Conclusion: AO-TFI enabled a detailed visualization and quantification of macular RPE and PR cells, providing valuable insights into the pathophysiology of AZOOR.